PENGARUH LABEL HALAL DAN KEAMANAN BAHAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI MAJESTYK BAKERY & CAKE SHOP BAKARAN BATU KECAMATAN LUBUK PAKAM - Iga Wahyuni; Sari Wulandari; Rukmini Rukmini; Nur'ain Harahap (Bisnis-Net, 2023)
This study aims to determine and analyze the effect of halal labels and material safety on purchasing decisions. The sampling technique used purposive sampling, amounting to 88 respondents. Methods of data collection using a questionnaire / questionnaire. Partial research results Material Safety has a significant positive effect on Purchasing Decisions. Simultaneously the Halal Label and Material Safety have a positive and significant effect on Purchasing Decisions with a calculated F value > F table with a significant value of 0.000, it can be concluded that the halal label variable and material safety simultaneously or together have a positive and significant effect on the purchasing decision variable. The results of the calculation of the coefficient of determination can be explained that the level of influence (R Square) of the halal label variable and the material safety variable on the purchasing decision variable is 0.700. It can be concluded that the halal label variable and the ingredient safety variable have an influence of 70% on the purchasing decision variable while the rest is influenced by other variables not examined in this study.Keywords: Halal label, material safety, purchase decision